Can white elephants kill? Unintended consequences of infrastructure development in Peru - Antonella Bancalari (Institute for Fiscal Studies (IFS), 2020)
It is widely accepted that investing in public infrastructure promotes economic development. However, there is little awareness of the prevalence of unfinished infrastructure projects and their consequences. In this paper, I study the effect of unfinished sewerage infrastructure on early-life mortality in Peru. I compile several sources of administrative panel data for 1,400 districts spanning 2005-2015, and I rely on the budgetary plans and timing of expenditure for 6,000 projects to measure unfinished projects and those completed in a given district. I document that mid-construction abandonment and delays are highly prevalent. I exploit geographical features and partisan alignment to instrument for project implementation. Surprisingly, I find that unfinished sewerage projects increased early-life mortality, driven by lack of water availability, water-borne diseases and accidents. I also show that while unfinished projects pose hazards to the population, completed sewerage projects decrease early-life mortality, in line with public health studies in advanced economies during the previous centuries.
Keywords: C36; H51; I15; J18; N36; O18; 330; infrastructure; public expenditure; sewerage; mortality; Peru